Global tuberculosis report 2015 - Anderson, Laura; Dean, Anna; Falzon, Denis; Floyd, Katherine; García Baena, Inés; Gilpin, Christopher; Glaziou, Philippe; Hamada, Yohhei; Hiatt, Tom; Kanchar, Avinash; Law, Irwin; Lienhardt, Christian; et al. (France : World Health Organization, 2015)
The designations employed and the presentation of the material in this publication do not imply the expression of anny opinion whatsoever on the part of the World Health Organization concerning the legal status of any country, territory,city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Dotted and dashed lines on mpas represent approcimate border lines for which there mary not yet be full agreement
Contents Abbreviations Acknowledgements Preface Executive Summary Chapter 1. Introduction Chapter 2. Disease burden and 2015 targets assessment Chapter 3. TB case notifications and treatment outcomes Chapter 4. Drug-resistan TB Chapter 5. Diagnostics and laboratory strengthening Chapter 6. Addressing the co-epidemics of TB and HIV Chapter 7. Financing Chapter 8. Research and development Annexes 1. Access to the WHO global TB database 2. Country profiles for 22 high-burden countries 3. Regional profiles for 6 WHO regions 4. Key TB indicators for individual countries and territories, WHO regions and the world
Incluye Contenido
Incluye Abreviaturas
Keywords: TUBERCULOSIS; PULMONES -- ENFERMEDADES; TUBERCULOSIS PULMONAR; BACILO DE KOCH